Review of Profit Management in Basic Material Companies in Indonesia Seen from the Perspective of Intellectual Capital, Financial Stability, Financial Distress, and Firm Size - Sari, Egi; Faisal, Yusuf; Febrianti, Adila (Universitas Nahdlatul Ulama Surabaya, 2025)
This study aims to determine the influence of intellectual capital, financial stability, financial distress and firm size on earning management. This study uses quantitative data, the sample in this study is 31 companies in the basic materials sector listed on the Indonesia Stock Exchange in the period 2012 – 2022. The analysis technique used to test the hypothesis was multiple regression analysis using Eviews 9 software. This study shows that the intellectual capital variable has a negative and statistically insignificant effect on earning management, the financial stability variable has a positive effect and is statistically insignificant on earning management, the financial distress variable has a positive effect on earnings management and the firm size variable has a positive effect and is statistically insignificant on earning management and statistically insignificant towards earning management